Effects of Scapular Circle Stretching on Muscle Activation and Scapular Posterior Tilt in Healthy Adults - Kyung-hee Jung; Il-young Moon; One-bin Lim; Chung-hwi Yi (Physical Therapy Korea)
Background: Passive or therapist-assisted stretching, followed by scapular stabilization exercises, has been shown to be effective. However, most previous studies have focused on stretching individual muscles or specific movement directions, often neglecting the role of active scapular stretching. Objects: This study aimed to compare changes in the muscle activity of the lower trapezius (LT), serratus anterior (SA), and upper trapezius (UT), as well as the scapular posterior tilt (SPT) angle before and after scapular circle (SC) stretching during SPT exercise. Methods: Twenty participants were recruited for this study. Electromyography electrodes were attached to the LT, SA, and UT. Muscle activity and the posterior scapular tilt angle were measured while performing the SPT exercises. After the SC stretch, the measurements were repeated in the same manner. The LT, SA, and UT electromyography activities and SPT angles were analyzed using paired t-tests. Results: LT activity was significantly higher in the SC stretch plus SPT exercise compared with in the SPT exercise alone (p = 0.018). There were no significant differences in SA activity between the SPT and SC stretch plus SPT exercise conditions (p = 0.812). UT activity significantly increased in the SC stretch plus SPT exercise compared with that in the SPT exercise (p = 0.001). The SPT angle was significantly enhanced during SPT exercise after the SC stretching compared to that without SC stretching (p = 0.009). The RSP improved by 2.32% compared to the initial posture when only the SPT was performed, and improved by 9.95% when the SPT was performed after the SC stretching. Conclusion: These results suggest that performing SC stretching prior to SPT exercise may effectively improve scapular alignment and posture, even when UT activation increases more than of the LT. Elevated UT activity highlights the need to address muscular balance in corrective exercise design.